2014
DOI: 10.1002/dvdy.24141
|View full text |Cite
|
Sign up to set email alerts
|

AP‐2α is required after lens vesicle formation to maintain lens integrity

Abstract: Background: Transcription factors are critical in regulating lens development. The AP-2 family of transcription factors functions in differentiation, cell growth and apoptosis, and in lens and eye development. AP-2a, in particular, is important in early lens development, and when conditionally deleted at the placode stage defective separation of the lens vesicle from the surface ectoderm results. AP-2a's role during later stages of lens development is unknown. To address this, the MLR10-Cre transgene was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…Among multiple candidate proteins, lens epithelial integrity is mediated by E- and N-cadherins and β-catenin ( Pontoriero et al, 2009 ). The early expression of cadherins is regulated by AP-2α (Tfap2a) ( Pontoriero et al, 2008 ), and loss of AP-2α after the formation of the lens vesicle results in the formation of an abnormal multilayered lens epithelium ( Kerr et al, 2014 ). As age-onset cataract is characterized by disrupted lens epithelium function, including epithelial cell loss (see Petrash, 2013 ), the continuation of studies related to lens epithelial homeostasis is crucial for understanding cataractogenesis.…”
Section: Differentiation Of the Lens Epitheliummentioning
confidence: 99%
“…Among multiple candidate proteins, lens epithelial integrity is mediated by E- and N-cadherins and β-catenin ( Pontoriero et al, 2009 ). The early expression of cadherins is regulated by AP-2α (Tfap2a) ( Pontoriero et al, 2008 ), and loss of AP-2α after the formation of the lens vesicle results in the formation of an abnormal multilayered lens epithelium ( Kerr et al, 2014 ). As age-onset cataract is characterized by disrupted lens epithelium function, including epithelial cell loss (see Petrash, 2013 ), the continuation of studies related to lens epithelial homeostasis is crucial for understanding cataractogenesis.…”
Section: Differentiation Of the Lens Epitheliummentioning
confidence: 99%
“…Previous studies have also shown an association between mutations in the Forkhead Box Protein E3 ( Foxe3 ) gene, and abnormal ocular phenotypes including Peters anomaly, microphthalmia, anophthalmia, and iris and retinal coloboma, in addition to sclerocornea (Garcia‐Montalvo et al, ). FOXE3 is expressed in the head ectoderm and lens epithelium of mice and adult mice that are homozygous null for Foxe3 show many features of other aforementioned genetic mutations, including a reduced lens size and a thicker anterior lens epithelium layer compared to controls (Kerr, Zaveri, Robinson, Williams, & West‐Mays, ; Medina‐Martinez et al, ). In addition, some mutants displayed corneolenticular adhesions and abnormally shaped nuclei of fiber cells within the lens, as well as retinal folding, missing corneal endothelium, disarrayed corneal stroma, and a reduction in thickness of the corneal epithelium (Medina‐Martinez et al, ).…”
Section: Rare Human Ocular Disorders and The Neural Crestmentioning
confidence: 99%
“…The TFAP2A gene has previously been linked to optic fissure closure defects and retinal abnormalities associated with coloboma, along with coloboma in the retina and choroid, as well as microphthalmia, iris coloboma, and sclerocornea in humans (Gestri et al, ). TFAP2A is a human homolog of AP‐2α, which is part of the activating protein 2 (AP‐2) family of transcription factors, consisting of a range of retinoic acid (RA) responsive proteins that includes AP‐2α, AP‐2β, AP‐2δ, AP‐2γ, and AP‐2ɛ (Bassett et al, ; Eckert, Buhl, Weber, Jäger, & Schorle, ; Kerr et al, ; West‐Mays et al, ). By E8.75, AP‐2α is expressed in the POM surrounding the optic vesicle of wild‐type mice, although expression ceases in this region after E10.5 (Bassett et al, ).…”
Section: Rare Human Ocular Disorders and The Neural Crestmentioning
confidence: 99%
See 1 more Smart Citation
“…Further in vitro studies showed that R120G mutation causes defective chaperone-like functions in alpha-B protein [10]. Beta-crystallins are expressed from the early developmental stages in the eye lens; their expression continues and increases after birth, so that the highest concentrations are found in the lens cortex [11]. The molecular basis of crystallin alpha B (CRYAB) gene expression has not been completely understood.…”
Section: Introductionmentioning
confidence: 99%